Water and steam injection in micro gas turbine supplied by hydrogen enriched fuels: Numerical investigation and performance analysis. (9th July 2021) - Reale, Fabrizio; Sannino, Raniero
Abstract: This paper investigates the energetic and environmental performance of micro gas turbine plant with two proposed concurrent improvements: the methane-based fuel enriched by hydrogen and the humidification of the plant cycle. The energetic and environmental benefits of both features are well-know, and the aim of this work is the analysis of their combined impact on the micro gas turbine operation. Despite enhancing fuel with H2 involves significant advantages like greenhouse emission reduction and a better combustion in case of low LHV fuels, most of commercial micro gas turbine combustors are not able to burn fuels with high hydrogen content unless structurally modified. On the contrary, has been demonstrated that humidified gas turbines (i.e., gas turbines with water injection, humid air turbine (HAT) and steam injection gas turbine (STIG) cycles) improve the combustion stability as well as electric power delivered and plant efficiency. Hence, in order to investigate the feasibility of the concurrent two features, the first step of this work was the thermodynamic analysis of a micro gas turbine supplied by methane-based fuels enriched with H2 up to 20%vol, considering both dry and humidified cycles. Since a combustion anomaly was detected, i.e., flashback, in the CFD study on the combustion chamber, a steam injection in the combustor has been added in the plant layout with the aim of overcoming the anomaly, and its effect on the combustion process has been analyzed also raising the hydrogen content up to 30%vol . The main outcome of this paper is the assessment of the feasibility of supplying the combustor of the proposed HGT-STIG micro gas turbine with a hydrogen enrichment up to 30%vol, achieving a safe and regular combustion mainly owing to a steam injection mass flow equal up to 125% of fuel flow. Highlights: The effect of H2 -enriched fuels in a 100 kW micro gas turbine plant is studied. The impact of humidified gas cycle on H2 -enriched fuels is investigated. The net power increased up to 20% compared to dry cycle. A humid-STIG cycle is proposed to overcome the occurring combustion anomalies. A noteworthy extension of plant operating domain is observed.